Implications of the Middle East Emerging Markets on International Portfolio Diversification - Mansourfar, Gholamreza (2010)
Solnik’s international portfolio theory suggests more benefits from diversification if investors invest internationally. The literature highlights that diversification benefits are more significant if equity investments from emerging markets are included in international portfolios. Using two different approaches, the advanced econometric techniques and a meta-heuristic optimization algorithm, this study evaluates the potential advantages of international portfolio diversification of Middle Eastern emerging markets. To investigate the long-run linkages and the short-run dynamics of equity markets the study relies on time series techniques of co-integration based on Vector Auto-Regressive framework, Impulse Response Functions and Variance Decompositions. For the optimization objective, Multiple-Fitness Function Genetic Algorithm procedures are applied to compute optimal portfolios based on both symmetric and asymmetric risk measurements and the long and short-run behavior of investments are investigated through the dominance of Efficient Frontiers. The countries included in this study are expanded in five stages. In the first stage, the analysis is done among six Middle Eastern countries. It is expected that the benefits of portfolio diversification among these countries would be significantly lower as compared to a sample extended by adding countries from Middle-East and North-Africa (MENA) and East Asian equity markets. In the stage four, analyses are done by including developed markets represented by the USA, the UK and Japan. Finally in stage five, all the above regions are considered together. The findings indicate that, contrary to expectations, the Middle East markets are not integrated regionally. For the intra-regional investments, the Middle Eastern equity markets provide more portfolio diversification benefits as compared to the emerging and developed equity markets. A vital difference between emerging and developed markets is that developed countries provide the opportunities of selecting the desired investments among a similar set of portfolio risks in both the short and long-term holding periods. However, the efficient frontiers offered by emerging markets do not have this advantage such that the risks of their optimal portfolios are restricted either in long or short-term. For the inter-regional investments, there is evidence that investors from emerging and developed markets gain by diversifying their portfolios with Middle Eastern equity markets. However, in the long-term, the Middle Eastern equities let investors to have a wider set of investment opportunities compared to the short holding period. The findings imply that the Middle East stock markets could be used as a hedge against the risk of oil price shocks especially for oil consuming economies. Despite the fact that Middle Eastern markets do provide opportunity for international diversification, in practice these countries are the smallest recipient of international portfolio inflows among other emerging regions. This implies that there are probably other factors, besides international diversification benefits, such as political instability, weak market micro-structure, and small market capitalization that explain the low inflow of international portfolio capital into these markets. It is crucial to note that international investors prefer to invest in markets that have low transaction costs, high market liquidity, wider choice of available investment instruments, better information dissemination, effective market regulation and trading mechanisms and selective investment restrictions need to be enforced by policy makers to make these markets more attractive for international investors.